550 A Systematic Review of Aesthetic Outcome Using Dermal Regeneration Templates in Nasal Reconstruction. (19th August 2022) - Bhatti, N; Jamshidi, S; Williams, G; Wormald, J; Wood, S; Dunne, J
Abstract: Aim: Nasal reconstruction using Dermal Regeneration Templates (DRT) has been proposed due to their ability to reduce contour defects, avoid donor site morbidity, and facilitate reconstruction. This review aims to determine the aesthetic outcomes of DRT's in nasal reconstruction. Method: A full systematic literature review of DRT use in nasal reconstruction was performed by two authors in December 2021. Cochrane Central Register of Controlled Trials, Ovid EMBASE and Ovid MEDLINE were searched and included papers reporting objective measures of aesthetic outcome. Of the 385 papers identified, 5 were included. Results: 75 patients were included. Defects resulted from excision of skin tumors (74) and vascular malformation (1). 1 study used Hyalomatrix, 1 used Integra or Matriderm and 3 used Integra only. 2 papers using Integra left the defect to heal secondarily without a skin graft and healing time was 6 weeks or less, while 3 studies performed a second stage with a full thickness skin graft at 2 weeks or later. Mean defect size was poorly reported, and several subunits were reconstructed. Using the Vancouver Scar Scale and Visual Analogue Cosmetic Scale, significant improvements compared to pre-operative assessment were observed and good to high patient satisfaction. Complications were infrequent. Subsequent flap reconstruction was performed in 12 patients. Conclusions: Nasal reconstruction using DRT is reliable however data on aesthetic outcomes are limited. The re-operation rate is reasonably high and data comparing aesthetic outcomes to flaps and skin grafts are lacking. More research reporting objective outcomes is warranted to further evaluate the utility of DRT's.